RELATIONSHIP BETWEEN BANKING SERVICE AND SETTLEMENT WITH MENTAL HEALTH OF XI CLASS 1 DUAPITUE STATE HIGH SCHOOL, SIDENRENG DISTRICT, RAPPANG - Mukhtar Saleh (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX Sulawesi, 2019)
The purpose of this study was to determine the relationship between Guidance and Counseling Services with Class XI Mental Health of Duapitue 1 High School in Sidenreng Rappang District. This study uses a pre-experimental method. The population of this study is the XI grade 1 SMA 1 Sidrap academic year 2018/2019. The sample is 20 students. Sampling uses purposive sampling in one class. It was found that there was a significant relationship between pre-test and post-test of student achievement in counseling services. Therefore, it can be concluded that there is a relationship between counseling services and mental health of Grade IX students of SMAN1 Sidrap.